PEMBELAJARAN VOKAL PADA PELAJARAN SENI BUDAYA DAN KETERAMPILAN DENGAN METODE SOLFEGIO DI KELAS V SD - Priyatna, Sukmana; Julia, Julia; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2017)
Vocal learning implementation should create learning process actively, creatively utilizing existing learning resources. Supported competencies teachers who are esperts in their field to study vocal. The condition of the school shows have used method to increaselearning solfegio vocals. Therefore the research needs to be done to get to know the process of learning the vocals. Objective to describe the process of use of methods of learning to solfegio vocals. A descriptive qualitative research methods with steps planning, implementation, observation, data processing and reflection, with the subject of research grade Va SDN Lebakwangi 01 Nagreg, and implementation timein half the space of 2016/2017. Data collection by observation, interviews, field notes and documentation. From the results of the use of research methods can improvevoal skills solfegio students. Recomemendation from the results of this study is throught use of vocal learning in solfegio method can be applied the primary to grade V.